The comparison of lignin content between Acacia (Acacia mangium) and Rubberwood (Hevea brasiliensis) / Mohd Azhar Mohd Zin - Mohd Zin, Mohd Azhar (2004)
The percentage of ligin in Acacia (Acacia mangium) and Rubberwood (Hevea brasiliensis) was determined and compared. This was done according to the TAPPI Standard Methods. From the experiment, lignin content was found to be 27.22% in Acacia and 29.95 % in Rubberwood. Thus Rubberwood presences higher lignin content when compared to Acacia. This result was followed the lignin content range for hardwood. These values of lignin content could serve as good indication for better utilization especially in the manufacture of chemical pulp. Lower lignin content is more suitable in papermaking manufacturing processes, and lead to better quality paper.